Transiently elevated expression of different forms of brain-derived neurotrophic factor in the neonatal medial prefrontal cortex affected anxiety and depressive-like behaviors in adolescence - Lanshakov, Dmitriy; Shaburova, Elizaveta; Sukhareva, Ekaterina; Bulygina, Veta; Drozd, Uliana; Larionova, Irina; Gerashchenko, Tatiana; Shnaider, Tatiana; Denisov, Evgeny V.; Kalinina, Tatyana (PeerJ, 2024)
Brain-derived neurotrophic factor (BDNF) is a secreted molecule that plays an important role in the survival and growth of nerve cells. BDNF undergoes complex post-translational processing with cellular proteases. Pro- and mature BDNF forms bind to different receptor types in the brain. BDNF is prominent in the neonatal cerebral cortex. The neonatal period is critical for the proper development of the brain and nervous system. Disruptions in these critical periods can have long-lasting effects on behavior and mental health. Individuals who experience adverse effects in the neonatal period have demonstrated a predisposition to depression and other neurobehavioral disorders. In this work we studied the influence of transient expression (P3–P8) elevation of pro-, mature and mutant forms of BDNF that could not be processed with cellular convertases in the neonatal medial prefrontal cortex (mPFC) on anxiety and depressive-like behavior in adolescents. Elevated expression of mature BDNF (LV-BDNF) increased anxiety and depressive-like behavior at P30. Only immobility in the tail suspension test was increased after expression of mutant BDNF (LV-pBDNF mut). Using our RNA-seq data and available online sn-RNAseq results, we investigated transcriptomic changes in the neonatal mPFC at P8 that underlie subsequent behavioral changes. Mature BDNF expression caused an increased transcriptional response in perivascular stromal cells (PSC) with such genes: Ptgds, Slc6a13, Slc22a6, Bnc2, Slc13a4, Aldh1a2. Based on GWAS data, Ptgds is a candidate gene associated with ADHD and bipolar disorder Pujol-Gualdo et al. (2021); Marín-Méndez et al. (2012); Munkholm et al. (2015). LV-pBDNF mut caused a complete opposite set of transcriptional changes in the PSC compared to LV-BDNF. The observed similar behavioral phenotype after expression of mature and mutant forms of BDNF together with the detected genes related to bipolar disorder underpinned that Bdnf could play a substantial role in the pathogenesis of this neurobehavioral disorder.
Keywords: Prefrontal cortex; Neonatal period; Juvenile period; RNAseq; Anxiety; Depression